Semantic Change in Historical Linguistics: Theories, Evidence, and Contexts - Buhari; Kumala, Sonya Ayu (Lingua : Journal of Linguistics and Language, 2024)
Semantic change has become an increasingly important focus in historical linguistics and sociolinguistics, reflecting how language evolves in response to social, cultural, and technological transformations. This narrative review aimed to synthesize conceptual, empirical, and contextual perspectives on semantic change and to assess the implications of these shifts for broader societal dynamics. Literature was systematically collected from major databases including Scopus, Web of Science, Google Scholar, and PubMed, using keywords such as semantic change, sociolinguistics, migration discourse, and linguistic evolution. Inclusion criteria emphasized peer-reviewed studies published in the past five years, complemented by seminal works providing historical context. The results reveal three interrelated themes: conceptual frameworks including semantic gradation and discourse-historical approaches; empirical patterns documented through quantitative analyses of lexical shifts and concreteness in language use; and contextual influences encompassing social policies, cultural traditions, and digital communication. These findings demonstrate that semantic change is not only a linguistic phenomenon but also a reflection of systemic structures, power relations, and cultural identities. The discussion highlights the need for inclusive language policies, culturally responsive education, and interdisciplinary research to mitigate inequalities and preserve linguistic diversity. By linking theory, data, and context, this review contributes to a more comprehensive understanding of semantic change and its relevance for language, society, and identity in a globalized world.